ANALISIS PERSEPSI KONSUMEN PADA PRODUK PERUMAHAN DI PT. CIPTA JAYA INHIL DI TEMBILAHAN - Ardian "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Sales promotion is the efforts made by the company in order to advise, inform about their company and products in the form of services and also products finished goods the Middle social life, consumers or clients, so that products to be recognized and used by customers with any form of advantage convenience and facilities granted promotion.This research was conducted in residential Al-Husna, located at JL. Weekend Arba Tembilahan. electoral Reasons this housing because it develops residential housing design, minimalist home with this type of interest. In this study the methodology used by the descriptive, where the samples used by the resident Housing is Al-Husna for as much as 60 heads of family, to determine the sample census, using techniques of data collection is through interview, observation and quesioner.From the results of analyzing the promotion execution carried out by Housing Al-Husna venues activities, including advertising and promotion, price and service, stating that the consumer's perception of development activities is at a category less fine. The perception of the activities already carried out still less capable of attracting consumers to know and take decisions in choosing housing Al-Husna Tembilahan.Key words: Analysis, Consumer Perceptions, Housing